2014
DOI: 10.1002/bjs.9544
|View full text |Cite
|
Sign up to set email alerts
|

Randomized clinical trial of isolated Roux-en-Y versus conventional reconstruction after pancreaticoduodenectomy

Abstract: NCT00915863 (http://www.clinicaltrials.gov/) and UMIN000001967 (http://www.umin.ac.jp/).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
58
1
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(64 citation statements)
references
References 40 publications
1
58
1
4
Order By: Relevance
“…The search strategy generated 217 relevant clinical studies, among which eight full text articles were identified for further investigation. Of these, two studies were excluded: one study only compared isolated Roux reconstruction with pancreaticogastrostomy, while the other study included general Roux reconstruction in the analysis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The search strategy generated 217 relevant clinical studies, among which eight full text articles were identified for further investigation. Of these, two studies were excluded: one study only compared isolated Roux reconstruction with pancreaticogastrostomy, while the other study included general Roux reconstruction in the analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Of these, two studies were excluded: one study only compared isolated Roux reconstruction with pancreaticogastrostomy, while the other study included general Roux reconstruction in the analysis. Finally, six studies were included, of which two were prospective randomized comparative studies , one prospective nonrandomized study and three retrospective comparative studies . The study selection process is shown in Figure .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A limitation of this study was the different understanding of the surgical reconstruction methods. Two studies compared conventional single loop reconstruction with ReY reconstruction [29, 31], while only one study intentionally compared ReY and BII, again favoring BII reconstruction [19]. However, differences regarding the local setting (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the advances in the surgical and postoperative management techniques, the risk of development of biliary fistula remains a problem after complex hepatobiliary surgery (1)(2)(3)(4)(5). An undrained biliary fistula may be further complicated by abdominal abscess formation and sepsis, necessitating long-term drainage or even surgical intervention (6).…”
Section: Introductionmentioning
confidence: 99%